PERHITUNGAN LABA/RUGI TOKO KELONTONG DI KELURAHAN TAMALANREA JAYA, KECAMATAN TAMALANREA, KOTA MAKASSAR, SULAWESI SELATAN - Masriani Mahyuddin; Eny Suprapti (J-MACC, 2022)
The purpose of this study is to provide empirical evidence that the grocery store business is very promising to be involved in in terms of the profit and loss calculation generated by not ruling out the weaknesses, advantages and obstacles faced, accompanied by proof of sales reports. This is based on the high level of small businesses spread across Tamalanrea Jaya Village, Tamalanrea District, Makassar City, South Sulawesi. This study uses a qualitative analysis approach. Previous research was conducted in Depok City, which has a much smaller population than Makassar City. The results of this study conclude that 1) grocery stores in Makassar City are included in the category of small businesses and are still traditional. 2) The profit of the grocery store is obtained from the reduction of total sales with the costs incurred to increase the stock of goods. 3) The bargaining system causes differences in profits even though the goods sold are the same goods. Further research should be on a wider area, more variables and forms of small and medium enterprises other than grocery stores.